2013
DOI: 10.1186/bcr3454
|View full text |Cite
|
Sign up to set email alerts
|

β1-integrin via NF-κB signaling is essential for acquisition of invasiveness in a model of radiation treated in situ breast cancer

Abstract: IntroductionDuctal carcinoma in situ (DCIS) is characterized by non-invasive cancerous cell growth within the breast ducts. Although radiotherapy is commonly used in the treatment of DCIS, the effect and molecular mechanism of ionizing radiation (IR) on DCIS are not well understood, and invasive recurrence following radiotherapy remains a significant clinical problem. This study investigated the effects of IR on a clinically relevant model of Akt-driven DCIS and identified possible molecular mechanisms underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…Indeed, recent studies showed that several integrins ( i.e. Itga2, Itga5, Itgb1, and Itgb4) are NFκB regulated (6469). These findings suggest that integrin-based cellular function ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies showed that several integrins ( i.e. Itga2, Itga5, Itgb1, and Itgb4) are NFκB regulated (6469). These findings suggest that integrin-based cellular function ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…36 Other authors showed that malignant phenotype emerged in a breast cancer model, characterized by upregulation of MMP-9, among other molecules, and loss of E-cadherin. 49 A noninvasive human lung tumor cells study demonstrated that E-cadherin upregulates MMP-2 and MMP-9 expressions at the protein level. 32 Those studies let us to think the positive correlation found in our results can be a coincidence biased by small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously reported that cancer cell invasiveness may be increased by IR in a surviving population after IR treatment. 16,17,39 Thus, we investigated the effect of RGD/ P-AuNPs on breast cancer invasion after radiation treatment. To evaluate the effect of RGD/P-AuNPs and radiation on the invasive activity of breast cancer cells, we performed a Matrigel chemoinvasion assay.…”
Section: Inhibition Of Radiation-induced Invasion By Rgd/p-aunps In Bmentioning
confidence: 99%